Adrenal crisis due to pembrolizumab-induced hypophysitis in a patient with triple-negative breast cancer - Sobrina S Mohammed; Sallam Alrosan; Reda Asad (Endocrine Oncology)
We report a case of a 43-year-old woman with stage IIB triple-negative breast cancer (TNBC) on neoadjuvant pembrolizumab presenting in adrenal crisis. Biochemical evaluation revealed isolated adrenocorticotropic hormone (ACTH) deficiency, and MRI demonstrated a partial empty sella; findings consistent with pembrolizumab-induced hypophysitis. Glucocorticoid replacement therapy led to symptom resolution. Pembrolizumab-induced hypophysitis is rare (incidence ∼0.98%), often associated with isolated ACTH deficiency, making diagnosis challenging due to nonspecific symptoms and frequently unremarkable pituitary imaging. As ICI use expands, clinician awareness of immune-related adverse effects (irAEs) is essential to prevent life-threatening complications and improve outcomes.